Hydrogen Peroxide Bleaching of Cationized Cotton Fabric. Issue 5 (September 2019) - Fu, Sha; Farrell, Matthew J.; Ankeny, Mary A.; Turner, Edwin T.; Rizk, Victoria
Hydrogen peroxide (H2 O2 ) is the most commonly used bleaching agent for cotton fabric. However, the conventional H2 O2 bleaching formula is not applicable for cationized cotton due to the low whiteness index after bleaching, fabric weakening, and a significant loss of cationic sites. In this work, magnesium sulfate (MgSO4 ) was added in the H2 O2 bleaching formula to stabilize the bleaching system for cationized cotton. Additionally, a screening experiment with temperature and time, and sodium hydroxide (NaOH), H2 O2, and MgSO4 concentrations as the factors, and whiteness index, bursting strength, and color strength from dyeing as the responses, was formulated. A statistical model was created using JMP software, which demonstrated how the bleaching conditions influenced the fabric properties. This procedure can be useful for bleaching cationized cotton in production settings.